Prevalence of Pseudomonas Species, Escherichia coli and Staphylococcus aureus in milk samples of apparently normal lactating cows at various cattle farms in Ibadan, Nigeria (2023)
This study was aimed at identifying the most significant bacteria isolates in the udder quarters as pathogenic causes of subclinical mastitis, and as well to investigate antibiotic sensitivity of the isolated organisms. The study was carried out at three cattle farm locations in Ibadan metropolis, Oyo State, Nigeria. A total number of 105 apparently healthy lactating cows without udder inflammation were sampled for milk; sampling by hand stripping was done after swabbing the teats with cotton wool dipped in alcohol and discarding the first stripping. Culture and isolation techniques, as well as biochemical tests of milk samples from the four quarters of udders of the 105 apparently healthy cows were carried out. In addition, an in vitro antibacterial sensitivity test was performed for six classes of antibacterial agents. A test of independent assessment (Chi-square test) was used to determine if association existed between the bacterial species collectively isolated and the affected animals (p = 0.716) or quarters (p = <0.000). The study established the presence of subclinical mastitis associated with known pathogens of which Pseudomonas species (67.9%), Staphylococcus aureus (53.6%) and Escherichia coli (14.3%) were most significant in decreasing order of quarter distribution in average percentages. The study further revealed differences in susceptibility of the various quarters and spread of infection. The isolated pathogens were generally most susceptible to the fluoroquinolones while varying degrees of resistance was a finding for other classes of antibacterial used possibly due to their prolonged and indiscriminate use; and this calls for caution by animal health care providers.